Poultry slaughterhouse waste management through anaerobic digestion with varying proportions of chicken litter - Sushant Bist; Ravi Nepal; Tejendra Regmi; Ram Kumar Sharma (Environmental Challenges, 2024)
Nepal's burgeoning poultry industry which is a key sector in its economy leads to a considerable generation of slaughterhouse waste (SHW), necessitating effective and sustainable disposal methods. This study explores anaerobic digestion as an optimal solution for poultry SHW management, aiming to produce energy-rich biogas while efficiently mitigating pollution in these facilities. Particularly, the feasibility and effectiveness of co-digestion with chicken litter (CL) were investigated to enhance biogas production and waste utilization. Four distinct runs of anaerobic digestion were performed, each utilizing varying substrate compositions with SHW to CL ratios of 1:0, 4:1, 1:1, and 1:4. Throughout the process, essential parameters, including total solids (TS), volatile solids (VS), biological oxygen demand (BOD5), pH, temperature, biogas generation, were meticulously measured. The cumulative biogas production for each run was as follows: 14.87 liters and a biogas yield of 88.73 ml/gVS with a 17.39 % VS reduction for Run 1, 25.98 liters and a biogas yield of 147.21 ml/gVS with a 28.64 % VS reduction for Run 2, 78.32 liters and a biogas yield of 314.69 ml/gVS with a 54.32 % VS reduction for Run 3, and 89.195 liters and a biogas yield of 344.36 ml/gVS with a 63.05 % VS reduction for Run 4. Notably, as the proportion of CL increased in the mixture from 4:1 to 1:1, a considerable VS reduction was observed. Furthermore, when the ratio of SHW to CL reached 1:1 and 1:4, a significant BOD5 reduction of 50 % and 63.13 % was achieved, respectively, surpassing previous runs. The results reveal that the addition of CL in an appropriate ratio effectively manages poultry SHW, with the optimum SHW:CL ratio for significant biogas yield lying between 1:1 and 1:4.